2000
DOI: 10.1080/03014223.2000.9518214
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of mosquitofish and black mudfish to a piscicide: Could rotenone be used to control mosquitofish in New Zealand wetlands?

Abstract: The comparative sensitivities of mosquitofish (Gambusia affinis) and black mudfish (Neochanna diversus) to the piscicide rotenone were investigated to determine whether it is feasible to use rotenone to control mosquitofish in wetlands inhabited by mudfish. Mosquitofish were exposed to four nominal rotenone concentrations (56, 79, 112, 158 µg.L -1 ) and the time taken for 50% (ET50) and 90% (ET90) of individuals to gasp at the water surface was recorded. Fish were removed from the rotenone at this stage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…A small pilot study conducted during the planning period found that P. caudimaculatus had a high resistance to the chemical (T. Rayner unpubl. data), consistent with results obtained for other poeciliids (Fabacher & Chambers 1972;Willis & Ling 2000). Susceptibility also varies greatly between non-target organisms (Ling 2003).…”
Section: Application Issuessupporting
confidence: 89%
See 2 more Smart Citations
“…A small pilot study conducted during the planning period found that P. caudimaculatus had a high resistance to the chemical (T. Rayner unpubl. data), consistent with results obtained for other poeciliids (Fabacher & Chambers 1972;Willis & Ling 2000). Susceptibility also varies greatly between non-target organisms (Ling 2003).…”
Section: Application Issuessupporting
confidence: 89%
“…Susceptibility of fish species to rotenone is known to vary substantially (e.g., Willis & Ling 2000). Lockett (1998) reviewed several toxicity studies, finding that concentrations of rotenone required to induce death varied widely between species of fish and also between the same species in different studies.…”
Section: Application Issuesmentioning
confidence: 98%
See 1 more Smart Citation
“…Most fish are killed, for example, by a rotenone concentration of about 0.5 ppm, but Gambusia apparently survive this concentration with little mortality (Bonham, 1946). Based on the times taken for 50% and 90% of individuals to gasp at the water surface under different rotenone concentrations, Gambusia is only about half as sensitive to rotenone as Neochanna diversus (Willis and Ling, 2000). Gambusia are more tolerant to ''Dursban'', an organic phosphorus insecticide, than the fish species Lepomis cyanellus and Notemigonus crysoleucas .…”
Section: Physical and Chemical Tolerancesmentioning
confidence: 98%
“…One galaxiid species has been tested for its sensitivity to rotenone and was significantly more susceptible than mosquitofish (Willis & Ling 2000). Any eradication project should assess the potential impact on non-target species in order to compare the relative merits of dispersed applications or rotenone baits.…”
Section: Effects Of Rotenone On Non-target Aquatic Species and Wildlifementioning
confidence: 99%